Family vs School: Where the Conflict Ends. A Study of Families on the Court against School in Lombardia - Michela Bettinelli; Roberta Cardarello (LED Edizioni Universitarie, 2019)
Conflict between the school and the family has become a topic of high importance but rarely investigated. This study deals with this conflict in the Italian context, examining the legal processes in the region of Lombardia, thus the litigation between the family and the school which ended at the Administrative Court (TAR) between 2010 and 2018. This study is an exploratory preliminary research which intends to investigate the quantity of cases of litigation between the families and school and categorize the cases according to motivation for the legal action and type of the school. Although we assumed that most cases are connected to children with special needs, analysis showed that families with children without any kind of diagnosis are referring to the court more often than the families of children with special needs. There were more students from secondary schools than students from primary school and, interestingly, students of lyceums seem to be the most represented group in the litigation. The results are discussed, and new lines of research are depicted in order to recognize when and why the conflicts start and how it can be prevented.